2008
DOI: 10.1038/sj.bjc.6604082
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of NF-κB potentiates the effect of the topoisomerase inhibitor CPT-11 on colon cancer cells

Abstract: NF-kB interferes with the effect of most anti-cancer drugs through induction of anti-apoptotic genes. Targeting NF-kB is therefore expected to potentiate conventional treatments in adjuvant strategies. Here we used a pharmacological inhibitor of the IKK2 kinase (AS602868) to block NF-kB activation. In human colon cancer cells, inhibition of NF-kB using 10 mM AS602868 induced a 30 -50% growth inhibitory effect and strongly enhanced the action of SN-38, the topoisomerase I inhibitor and CPT-11 active metabolite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…In patients with colorectal cancer, CPT-11 (irinotecan), a topoisomerase inhibitor, can induce chemoresistance in malignant cells via activation of the NF-κB pathway (36)(37)(38). DNA topoisomerases are molecules that modulate chromosome superstructure and integrity via cutting, shuffling DNA strands, removing DNA supercoils, and disentangling snarled DNA segments (39).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with colorectal cancer, CPT-11 (irinotecan), a topoisomerase inhibitor, can induce chemoresistance in malignant cells via activation of the NF-κB pathway (36)(37)(38). DNA topoisomerases are molecules that modulate chromosome superstructure and integrity via cutting, shuffling DNA strands, removing DNA supercoils, and disentangling snarled DNA segments (39).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oleanolic acid also inhibited topoisomerase I and IIα proteins, which are key enzymes involved in tumor cell proliferation, by relaxing DNA supercoiling inside cells [63]. It has been demonstrated that topoisomerase inhibition activates the NF‑κB pathway [79]. The suppression of Top-I and Top-IIα resulted in the inhibition of the NF‑κB pathway via p‑IκBα and p‑p65‑dependent manner [63].…”
Section: Oleanolic Acid As Anticancer Agentmentioning
confidence: 99%
“…MiR-125, especially miR-125b, has been reported to be regulated by NF-kb depending on the cellular context (27,28). Meanwhile, cytotoxic chemotherapies such as CDDP, ETP, and CPT-11 are well known for activating NF-kb (29)(30)(31). In this context, although we could not demonstrate the significant HER2 upregulation by treatment with ETP, we suppose that chemotherapy exposure first induces NF-kb activation and correspondingly downregulates miR-125a and miR-125b expressions.…”
Section: Discussionmentioning
confidence: 99%